Determination of functionally important sequence variants in promoter sequence of homogentisate geranylgeranyl transferase from Elaeis guineensis Jacq. germplasm materials - Karim, Mohd Shahrul Nizwanshah (2020)
Vitamin E consists of tocopherols and tocotrienols which are lipid-soluble compounds produced by plants with various beneficial medicinal properties. Tocotrienols have cholesterol-lowering and anticancer properties and alpha-tocotrienols can prevent inducible neurodegeneration. There is high variability in the level of vitamin E in the E. guineensis germplasm materials from Angola and Tanzania ranging from 300-1600 ppm, while the level is 500-1000 ppm in the commercial variety. However, the development of markers for tocotrienols rich oil palm is still very scarce and the understanding of the regulation of vitamin E biosynthesis is important for genetic improvement specifically nutritionally vitamin E rich oil palm. Therefore, this study aimed to identify the SNPs in the promoter of HGGT that associate with the high vitamin E in E. guineensis germplasm materials. Homogentisate geranylgeranyl transferase (HGGT) is an important vitamin E biosynthetic enzyme that catalyses the first committed step for tocotrienols biosynthesis. Sequence alignment of 14 accessions from Angola and Tanzania with varying levels of vitamin E content showed the presence of an SNP (-454) that associate with high vitamin E Angolan (AH) and Tanzanian (TH) palms and two SNPs, -781 and -113 unique to AH. Functional characterisation to determine the roles of SNPs in influencing HGGT promoter activity was carried out by reporter gene assay in mesocarp tissues bombarded with four different HGGT promoter constructs. The pBGWFS7 vector used for cloning the HGGT promoter fragments contains two reporter genes, a green fluorescent protein (GFP) and GUS. The promoters were commercial DXP (COM), AH1, TH96 and a mutated derivative of COM (CM, g.-454A>G) produced by introducing the variant found in common in AH1 and TH96. The quantitative fluorometric GUS assay on GFP positive bombarded tissues shows that the lowest expression level was obtained from COM with GUS expression of 0.27 pmol MU min-1 mg protein-1 per copy numbers. The expression level obtained for COM is about the same as the constitutive CaMV 35S promoter that was used for comparison. There was no significant difference in the GUS expression level between the COM with the CM (g.-454A>G). The results showed that AH1 gave the highest GUS expression of 0.82 pmol MU min-1 mg protein-1 per copy numbers. It suggested that the CAAT-box unique to AH at the SNP (-113), a well-known proximal promoter element may enhance HGGT promoter activity and the tocotrienols content in AH1. Taken together, these studies have provided valuable information on the vitamin E biosynthetic regulatory mechanism in oil palm germplasm as these results suggest that the HGGT promoter is potentially useful for engineering of high vitamin E markers through SNPs association and it is essential for the future genetic improvement effort to produce high vitamin E oil palm.